ENHANCING THE NUMERACY SKILL OF THE PRE-SERVICE TEACHERS THROUGH STEM DESIGN-BASED LEARNING - Khaola Rachma Adzima; Puspita Sari; Nilam Novita Sari; Tiara Husnul Khotimah (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2026)
Based on the 2018 PISA results, Indonesian students' numeracy skills remain low, with the majority not reaching the basic proficiency level. One innovative approach is STEM design-based learning, which integrates aspects of Science, Technology, Engineering, and Mathematics into the learning process. While STEM has often been implemented in schools, its application in higher education remains limited. This study aims to analyze the effectiveness of the STEM design-based learning in enhancing the numeracy skill of pre-service teachers. The research population comprised sixth-semester students of the Mathematics Education undergraduate program at Universitas Negeri Jakarta, with a sample of 25 students. Data were collected through numeracy tests administered before (pre-test) and after (post-test) the implementation of the STEM design-based learning. Data analysis using a t-test, t(25) = 6.3189 with a p-value = 7.818 × 10⁻⁷ (p < 0.05), indicating that the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted, it means that the post-test scores were significantly higher than the pre-test scores. Then, the Cohen’s d-value was 1.26, indicating that the treatment had a very large effect on improving the numeracy skill of the pre-service teachers.